Diagnostic Evaluation of Pelvic Inflammatory Disease - Jeffrey F. Peipert; David E. Soper (Hindawi Limited, 1994)
Pelvic inflammatory disease (PID) is a serious public health and reproductive health problem in the United States. An early and accurate diagnosis of PID is extremely important for the effective management of the acute illness and for the prevention of long-term sequelae. The diagnosis of PID is difficult, with considerable numbers of false-positive and false-negative diagnoses. An abnormal vaginal discharge or evidence of lower genital tract infection is an important and predictive finding that is often underemphasized and overlooked. This paper reviews the clinical diagnosis and supportive laboratory tests for the diagnosis of PID and outlines an appropriate diagnostic plan for the clinician and the researcher.